1991
DOI: 10.1289/ehp.9193247
|View full text |Cite
|
Sign up to set email alerts
|

Chemicals associated with site-specific neoplasia in 1394 long-term carcinogenesis experiments in laboratory rodents.

Abstract: The carcinogenicity data base used for this paper originated in the late 1960s by the National Cancer Institute and since 1978 has been continued and made more comprehensive by the National Toxicology Program. The extensive files contain among other sets of information detailed pathology data on more than 400 long-term (most often 24 month) chemical carcinogenesis studies, comprised of nearly 1600 individual experiments having at least 10 million tissue sections that have been evaluated for toxicity and carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(32 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Dye production and use; clinical laboratories [220,247] Group 1 [76] 1 Not all of them are to be referred to group Non-infective risk As 7440-38-2 Timber manufacturing; pesticide use; As extraction industry; lead processing; pharmaceutical industry; glass industry; leather preservatives; antifouling paints; agrochemical production; microelectronics and optical industries; non-ferrous metal smelters; coal-fired power plants [254][255][256][257][258] Group 1 [263] Cd 7440-43-9 Cd mining; manufacturing of Cd-containing ores and products; Ni-Cd battery manufacturing, Cd alloy production [275,277,278] Group 1 [263] As: Arsenic; Cd: Cadmium; IARC: International Agency for Research on Cancer; CAS No. : Chemical abstract service number.…”
Section: -87-5mentioning
confidence: 99%
See 1 more Smart Citation
“…Dye production and use; clinical laboratories [220,247] Group 1 [76] 1 Not all of them are to be referred to group Non-infective risk As 7440-38-2 Timber manufacturing; pesticide use; As extraction industry; lead processing; pharmaceutical industry; glass industry; leather preservatives; antifouling paints; agrochemical production; microelectronics and optical industries; non-ferrous metal smelters; coal-fired power plants [254][255][256][257][258] Group 1 [263] Cd 7440-43-9 Cd mining; manufacturing of Cd-containing ores and products; Ni-Cd battery manufacturing, Cd alloy production [275,277,278] Group 1 [263] As: Arsenic; Cd: Cadmium; IARC: International Agency for Research on Cancer; CAS No. : Chemical abstract service number.…”
Section: -87-5mentioning
confidence: 99%
“…Burning municipal waste leads to inhalation of Cd. Workers in the metal and plastic product industry and workers involved in the construction of solar panels are exposed to Cd [277,278] . In 2011, Cd production was estimated to be 600 metric tons in United States.…”
Section: Cadmiummentioning
confidence: 99%
“…The liver is the most common site of tumor origin in experimental animals exposed to carcinogenic chemicals [18]. Moreover, some epidemiological studies on cancer incidence and mortality have shown that individuals in occupations that involve exposure to chemicals are at a higher risk of developing primary liver cancer [19].…”
Section: Introductionmentioning
confidence: 99%
“…Sites of tumor formation in humans show some similarities to those produced in rodent carcinogenicity bioassays (Huff et al, 1991). The lung, hematopoetic system, mammary gland, urinary bladder, and uterus are among the ten most frequent sites of tumor development in both the United States population and in rodent bioassays.…”
Section: A Animal Studiesmentioning
confidence: 90%
“…Over 400 long-term chemical carcinogenesis studies using rats and mice have recently been reviewed (Huff et al, 1991), and some similarities in incidence and site of tumor development were found. For example, in both species of rodents, liver is the most common tumor site, and, although mice are more likely to experience liver tumors, there is an 80% interspecies concordance for hepatocarcinogenicity.…”
Section: A Animal Studiesmentioning
confidence: 99%